Penerapan ISO 9001:2015 untuk Peningkatan Layanan Website BMKG.GO.ID dalam Mendukung Penyebaran Informasi Bencana Gempa Bumi - Dwi Hastanto, Andriana; Rustianto, April (LPPM STT Terpadu Nurul Fikri, 2024)
ISO 9001:2015 is an international standard or guideline for Quality Management Systems (QMS). The application of QMS is not limited to a particular industry and can be adapted to the nature, type, and size of the organization. This research is an academic study of the implementation of ISO 9001:2015 for services provided by the website www.bmkg.go.id. Especially to support the dissemination of earthquake information. The variable of this research is the perception of user satisfaction which was collected through a survey by PUSJARKOM BMKG on March 15, 2022. It consists of four research questions or instruments, the answers to each question are in the form of a perceptual narrative which is then assigned a value or weight based on a Likert Scale. PUSJARKOM BMKG uses the Likert Scale modification technique by eliminating neutral alternatives so that the respondents' answers are clear. With as many as 753 respondents, it was successfully obtained for the service satisfaction value of 94.5%, the service suitability value of 98.4%, the service speed value of 95.4%, and the service trust value of 77.2%. The results of the questionnaire were tested for validity and reliability using statistics with the help of Python software. The validity for each of these instruments is valid, and the reliability of the research variables is declared reliable based on Cronbach's Alpha value of 0.652.